Pengaruh Kepemimpinan Instruksional Dan Motivasi Kerja Guru Terhadap Kualitas Pembelajaran Sekolah Penggerak SMA Negeri Kota Semarang - Suratmin, Suratmin; Soegeng Ysh, A. Y.; Kusumaningsih, Widya (Jayapangus Press, 2025)
Education report card data shows that the quality of learning in the indicators of learning methods and teacher motivation is not optimal. There is still a gap in each school that has the status of a school mover. The objectives of this study are: (1) to analyze the influence of instructional leadership on the quality of learning, (2) to analyze the influence of teachers' work motivation on the quality of learning, and (3) to analyze the joint influence of instructional leadership and teachers' work motivation on the quality of learning of the Semarang City State High School Mover. Quantitative research approach with survey method. Type of correlational research. The research population is 270 teachers and the research sample is 162 teachers. Data collection with questionnaires. Data analysis techniques with descriptive data analysis, prerequisite tests including normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests and hypothesis tests including simple and multiple linear regression. The results of the study showed that: (1) the influence of instructional leadership on the quality of learning was 45.50%, with the regression equation Ŷ = 44.388 + 0.756X1 with a correlation coefficient value of 0.455. (2) the influence of teacher work motivation on the quality of learning was 36.80%, with the regression equation Ŷ = 56.466 + 0.758 X2 with a correlation coefficient value of 0.368. (3) the influence of instructional leadership and teacher work motivation on the quality of learning was 51.40%, with the equation Ŷ = 24.383 + 0.543 X1 + 0.384 X2. Then the correlation coefficient value r is 0.514. The conclusion of this study is that instructional leadership and teacher work motivation have an effect on the quality of learning by 51.40%.